Cerebral Malaria: Current Clinical and Immunological Aspects - Albrecht-Schgoer, Karin; Lackner, Peter; Schmutzhard, Erich; Baier, Gottfried (Frontiers in Immunology, 2022)
This review focuses on current clinical and immunological aspects of cerebral malaria induced by Plasmodium falciparum infection. Albeit many issues concerning the inflammatory responses remain unresolved and need further investigations, current knowledge of the underlying molecular mechanisms is highlighted. Furthermore, and in the light of significant limitations in preventative diagnosis and treatment of cerebral malaria, this review mainly discusses our understanding of immune mechanisms in the light of the most recent research findings. Remarkably, the newly proposed CD8+ T cell-driven pathophysiological aspects within the central nervous system are summarized, giving first rational insights into encouraging studies with immune-modulating adjunctive therapies that protect from symptomatic cerebral participation of Plasmodium falciparum infection.